Immune checkpoint inhibitors improve the efficacy of neoadjuvant chemotherapy in advanced gastric cancer: a retrospective cohort study - Yonghe Chen; Yi Lin; Yingying Xu; Jianwei Zhang; Shi Chen; Shuai Ye; Gang Liu; Lei Lian; Junsheng Peng (Therapeutic Advances in Medical Oncology)
Background: Immune checkpoint inhibitors (ICIs) have demonstrated efficacy in metastatic gastric cancer. Their potential benefits in the neoadjuvant therapy for advanced gastric cancer (AGC) are promising but require real-world evidence. Objective: We aimed to assess the real-world impact of adding ICIs to neoadjuvant chemotherapy (NAC) in AGC patients. Design: This is a retrospective, propensity score-matched analysis of 580 AGC patients treated with NAC, with or without ICIs, followed by radical gastrectomy. Methods: Patients were matched using propensity score matching (PSM) to balance baseline characteristics. Pathological complete response (pCR) rates and toxicity were compared between the ICIs-Chemo and Chemo cohorts. Results: After PSM, 188 patients were included: 71 in the ICIs-Chemo cohort and 117 in the Chemo cohort. Chemotherapy regimens in both cohorts included SOX (49.5%, 93/188), FLOT (26.6%, 50/188), XELOX (12.8%, 24/188), and FOLFOX (11.2%, 21/188). The ICIs used were predominantly Sintilimab (67.6%, 48/71), followed by Tislelizumab (21.1%, 15/71), Nivolumab (7%, 5/71), and others (4.2%, 3/71). Adding ICIs to NAC significantly improved the pCR rate (ICIs-Chemo: 29.6% vs. Chemo: 13.7%, p  = 0.014). The SOX regimen, with (37.1%, 13/35) or without ICIs (22.4%, 13/58), demonstrated the highest pCR rates. Subgroup analysis indicated that patients older than 60 years (OR = 3.86, p  < 0.01) and those with moderately/well-differentiated tumors (OR = 4.27, p  = 0.01) may derive greater benefit from adding ICIs. While overall toxicity and surgical complication rates were similar between cohorts, we observed two cases of suspected severe immune-related adverse events (irAEs). Conclusion: Adding ICIs to NAC regimens in AGC significantly improves pathological response. While overall toxicity is not increased, close monitoring for irAEs is necessary.